Metastatic spitzoid melanoma in a 6-year-old girl. - Rojas Angarita, P.; Leal Reina, S.; Rodriguez-Lechtig, B.; Rueda Cadena, X. (European Journal of Pediatric Dermatology, 2025)
Spitzoid melanoma is an extremely rare melanocytic neoplasm in childhood and is often difficult to distinguish clinically and histopathologically from other spitzoid lesions. We present the case of a 6-year-old girl diagnosed with pediatric spitzoid melanoma harboring a BRAF V600E mutation, with regional lymph node metastasis. The patient was treated with pembrolizumab and local cryotherapy for palliative purposes. Due to disease progression, targeted salvage therapy was initiated. The patient remains under multidisciplinary follow-up, has tolerated treatments well, and has shown no evidence of visceral progression to date. This case highlights the diagnostic complexity of spitzoid melanocytic tumors in pediatric patients and emphasizes the importance of integrating histologic and molecular findings to guide therapeutic decisions.